DINAMIKA DAN STRATEGI INFLUENCER DALAM MEMPERTAHANKAN KEBERHASILAN KARIR PADA INDUSTRI TERSATURASI - Jamaluddin, Putri Arsidah; Mau, Muliadi; Akbar, Muhammad (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
This research aims to analyze the dynamics and strategies used by influencers to maintain career success in an increasingly competitive social media industry. With the rise of internet access and social media usage in Indonesia, the influencer phenomenon has become an important force in marketing and communication. This study identifies two main focuses: first, how influencers face competition in a saturated industry, and second, the strategies employed to maintain credibility and relevance. Through a qualitative approach, this study explores how influencers shape their identities and create authentic content to build trust with their audience. The results indicate that authenticity, consistency, and meaningful interaction are key to long-term success. These findings are expected to contribute to the development of communication theory as well as provide practical insights for professionals in marketing and brand management. This research also offers a framework for understanding the dynamics of the influencer industry and its relevance in the ever-evolving context of digital marketing. Keywords: Keywords: Influencer, Social Media, Authenticity, Marketing Strategies, Credibility